Europe's great depression: Coordination failure after the first World War - Nikolaus Wolf (Center for Economic Studies and ifo Institute (CESifo), 2010)
In this paper I survey and reinterpret the extensive literature on Europe's Great Depression. I argue that Europe could not exploit her vast economic potential after 1918, because the war had not yet come to an end - indeed it did not end before 1945. Both, domestic and international institutions suffered from a lack of reciprocal trust and commitment, which can be clearly illustrated in the realm of monetary policy but affected many other areas of policymaking, such as energy or migration policies. These institutions in turn affected expectations and thereby the extent to which for example expansionary policies could be effective.
Keywords: E50; F50; N14; 330; Great Depression; Europe; coordination failure; Konjunktur; Wirtschaftskrise; Wirtschaftsgeschichte; Politischer Konflikt; Internationale wirtschaftspolitische Koordination; Staatsversagen; Europa